The Material from Western Asia and the Chronology of the Nineteenth Dynasty - Rowton, Michael В.
I. The Mesopotamian King-Lists; II. The Evidence of KUB I 1-10 and of KBo I 10; III. The Kvidence of KBo I 14 and KUB XXVI 70; IV. Chronicle P; V. The Determining Factor.